FAKTOR DOMINAN MEMPENGARUHI INFLASI DI INDONESIA - Syaipan Djambak (Department of Development Economics, Universitas Sriwijaya, 2008)
Inflation is a macro-economic disease that can damage the economy joints , damage the climate in production, and weaken purchasing of community. Because such damage to the economy as a result of high inflation, the monetary authority always tried to recruit all of the potential for inflation to avoid a major. Throughout historyÂ of Indonesian economy until the end of the year 2006, the average inflation rate (over 27 years) reached 11.03% of the inflation level is high enough, even 1966 years old indonesia inflation reached 650% and inflation reached 120% in 1967, and inflation in 1998 reached 77.63%.Based on existing conditions in inflation, the formulation of the problem examined in this research is:â€œWhat is the dominant variableÂ that influence of inflation in Indonesiaâ€Based on the theoretical study of several publications and research results, it appears that there are 7 (seven) variables that affect inflation, like: increase in production costs, increase in food prices, increase the amount of money circulating, the government budget deficit, inflation expectations, exchange rates depreciation,andÂ income growth.To find out the dominant variable affecting inflation in Indonesia,so it used the equationÂ modelÂ multiple regression, as follows:Inf = Î± M1 + ÃŸ Y/C + Â¥ Dep-Rp + Â£ Inf t-1+ Âµi. The result of calculation with the OLS show:Inf =Â 12,936 + 1,190 Y/c + 0,254 M1 + 0.58 Dep-Rp + 0,116 Inf t-1.After the calculation, the relationship of independent variables increase the amount of money circulating, increased percapita income, increased the value of dollar depreciation, inflation expectations and public adaptip marked positive, this means if there is an increase of the independent variables (increase the amount of money circulating, increased in percapita income, increased rupiah depreciation rate, and inflation expectations adaptip community) then inflation will increase, this was in accordance with the theory. But in partial, only variable percapita income that have significant effect on the inflation in Indonesia. The results of this research provides a description of consumption behavior of Indonesian community , where the percapita income is relatively low (still less than Rp 10 million in a year) and the level of inflation is relatively high above 5% in a year, causing an increase in income directly translated to the increase in public consumption. Key Words: Inflation, income growth, dominantÂ variable.